Kekerasan Terhadap Asisten Rumah Tangga Dalam Prespektif Krimilogis : Studi Polresta Kota Bandar Lampung - Cindy Pasela; Emilia Susanti; Gunawan Jatmiko (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Violence against domestic helpers is one form of crime that often occurs. This is certainly influenced by various factors and relates to the extent to which countermeasures for the crime are carried out. The purpose of the study is to find out what are the factors and efforts to overcome violence against domestic assistants. This study uses empirical juridical and normative juridical approaches. The results of this study show that the factors causing violent crimes against domestic helpers are environmental factors (differential association), economic factors (anomie theory), and religious factors (control theory) which can be overcome through penal and non-penal efforts.